(untitled) (Revista Contexto & Saúde, 2023)
This study analyzed the quantity of hypertension and diabetes drugs that return to health facilities, in and out of validity, in the form of disposal, in order to measure waste. Survey forms reflected on the population’s knowledge of unnecessary acquisitions, the consequences of incorrect disposal and the waste of public resources. The diabetes medication that most returned was metformin and the hypertension medication was furosemide. The representative of the cost of waste was spironolactone. The lowest cost in waste was hydrochlorothiazide. It is concluded that the most returned medicine does not necessarily represent the greatest cost in waste and that the problem with disposal is much greater because most of it is made in common garbage, toilets and sinks, making it difficult to quantify it.